Organizational aspects of improved irrigation management: Kalankuttiya Block, Mahaweli system H, Sri Lanka - Moragoda, R.; Groenfeldt, D. (International Irrigation Management Institute, 1990)
This report documents part of an operational experiment in Kalankuttiya Block of Mahaweli System H during the 1987 yala (dry season). The experiment or "action research" was conducted by the International Irrigation Management Insti tute (IIMI) in cooperation with the Mahaweli Economic Agency of the Mahaweli Authority of Sri Lanka. The experiment was the outgrowth of studies which focused on constraints to non-rice crops during the dry season. Careful monitoring of irrigation and cropping patterns in selected areas of the system, conducted from yala 1985, had documented three important constraints to di versified crops: 1) inadequate water control at the secondary and tertiary levels of the system, 2) lack of organization for water sharing from the secondary level downward, and 3) poor conununication between farmers and agency staff regarding water delivery schedules